1991
DOI: 10.1017/s0952523800004041
|View full text |Cite
|
Sign up to set email alerts
|

Visual-field map in the callosal recipient zone at the border between areas 17 and 18 in the cat

Abstract: The representation of the visual field in the callosal fiber recipient zone of area 17 and the adjacent area 17/18 transition zone was determined in the cat. The callosal fiber recipient zone was identified by anterograde transport of tritiated amino acids that had been injected into transcallosal sending zone of the opposite hemisphere. Application of autoradiographic procedures revealed that transcallosal projections are densest in the area 17/18 transition zone, and that their density in area 17 diminishes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
24
0

Year Published

1994
1994
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 46 publications
(87 reference statements)
7
24
0
Order By: Relevance
“…That CCs promote the integration of collinear lines crossing the VM has been described previously (Payne, 1994;Kiper et al, 1999;Knyazeva et al, 1999;Carmeli et al, 2007;Makarov et al, 2008;Schmidt et al, 2011). Noteworthy, the present study indicates that the stimulus does not even have to exceed RF borders to unveil orientation and direction-specific callosal influences.…”
Section: Ccs Are Selective For the Direction Of Movementsupporting
confidence: 82%
See 2 more Smart Citations
“…That CCs promote the integration of collinear lines crossing the VM has been described previously (Payne, 1994;Kiper et al, 1999;Knyazeva et al, 1999;Carmeli et al, 2007;Makarov et al, 2008;Schmidt et al, 2011). Noteworthy, the present study indicates that the stimulus does not even have to exceed RF borders to unveil orientation and direction-specific callosal influences.…”
Section: Ccs Are Selective For the Direction Of Movementsupporting
confidence: 82%
“…Further, the callosally interconnected zone becomes broader at elevations higher than Ϯ5° (Payne, 1994). Accordingly, when separating neurons according to their RFs' elevation, we observed that averaged differences in the MI differences between IN and OUT and also UP and DOWN directions persist and become even slightly larger in the farther away group (lower field 5-10°; Fig.…”
Section: Callosal Input Close and Farther Away From The Midlinesmentioning
confidence: 69%
See 1 more Smart Citation
“…In mammals with frontal eyes, the regions of area 17 sending projections to and receiving from the corpus callosum contain a binocular representation of the central portion of the visual field, comprising the vertical meridian (VM) and portions of the visual field on either side of the VM. Callosal connections within this representation would be maintained during development because visual stimuli presented along the VM would be activated in a synchronous and congruous manner for both the callosal and the thalamocortical pathways (Hubel and Wiesel, 1967;Berlucchi and Rizzolatti, 1968;Berlucchi, 1981;Lepore and Guillemot, 1982;Payne, 1990Payne, , 1991Payne and Siwek, 1991; for reviews see Innocenti, 1986;Houzel and Milleret, 1999). A generalization of this hypothesis, supported by anatomical evidence, suggests that matched retinotopy between callosal and intrahemispheric projections, not necessarily linked to the VM representation, could be the driving force for the stabilization of callosal connections during development (Olavarria, 1996;Bosking et al, 2000).…”
mentioning
confidence: 98%
“…First, although the cells that project through the corpus callosum are fairly widespread, their terminals are strongly focused on a narrow transition zone (TZ) between areas 17 and 18 that is part of neither area (Payne, 1990(Payne, , 1991Payne and Siwek, 1991). This transition zone represents the ipsilateral visual field principally through the contralateral eye, owing to the fact that a region of temporal retina near the area centralis projects both contralaterally and ipsilaterally.…”
mentioning
confidence: 99%